A review on the Durability of Recycled Asphalt Mixtures Embraced with Rejuvenators - Putra Jaya, Ramadhansyah; Al-Saffar, Zaid Hazim; Haryati, Yaacob; Katman, Herda Yati; Mohd Khairul Idham, Mohd Satar; Bilema, Munder; Eltwati, Ahmed Salama; Radeef, Hassanain Radhi (MDPI, 2021)
Reclaimed asphalt pavement (RAP) has received much attention recently due to its increased use in hot mix asphalt (HMA) pavements to enhance pavement sustainability. The use of aged asphalt in RAP, which is highly oxidised and has lost its properties due to exposure to traffic loads and climatic conditions throughout its lifespan, can cause asphalt mixtures to stiffen and embrittle, thus negatively affecting the behaviour of asphalt mixtures. This issue may be resolved by including rejuvenating agents that can restore both physical and rheological properties of aged asphalt by increasing maltene fractions and decreasing asphaltene. However, the high restoration capacity of any kind of rejuvenating agent does not assure the durability of restored aged asphalt. This study explored the performance and durability of rejuvenated asphalt mixtures embedded with several types of rejuvenators identified from the extensive literature review. The study serves as a significant reference to predict future challenges in rejuvenating aged asphalt.